2022
DOI: 10.1111/jocn.16239
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of clinical skill development of preregistration registered nurses in Australia and five other English‐speaking countries

Abstract: Aim The aim of this scoping review is to synthesise current evidence around the clinical skill development of preregistration registered nurses (RNs) in Australia, United Kingdom (UK), Ireland, United States (US), Canada and New Zealand, to inform nurse education, policy and clinical practice. Background Nursing is a practical profession, and registered nurses require specific skills, knowledge and attributes in order to care for patients safely. The context for health care delivery is shifting, and the educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 148 publications
2
13
0
1
Order By: Relevance
“…Factors that can influence the student being ready to practice include the effectiveness of academic clinical experiences and paid healthcare positions while in school ( Harrison et al, 2020b ). The quality of the educational experience (didactic, clinical, and simulation) is not completely understood, and it has been identified that there is a need for more robust research for how to prepare the next generation of nurses for the clinical setting ( Currie et al, 2022 ; Ironside et al, 2014 ). Tinôco et al (2021) performed a virtual educational intervention on nursing students and determined that effective use of both virtual and face-to-face characteristics in addition to effective educational interventions can lead to the development of clinical reasoning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that can influence the student being ready to practice include the effectiveness of academic clinical experiences and paid healthcare positions while in school ( Harrison et al, 2020b ). The quality of the educational experience (didactic, clinical, and simulation) is not completely understood, and it has been identified that there is a need for more robust research for how to prepare the next generation of nurses for the clinical setting ( Currie et al, 2022 ; Ironside et al, 2014 ). Tinôco et al (2021) performed a virtual educational intervention on nursing students and determined that effective use of both virtual and face-to-face characteristics in addition to effective educational interventions can lead to the development of clinical reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…An urgent demand exists for practice partners to respond to the needs of new graduate nurses and their transitions, as they will need to develop a sense of salience in this new healthcare world. As one student asked, “How do you nurse in the 21st century?” Support is needed for a student to become confident, satisfied, and competent in the role of the nurse ( Currie et al, 2022 ; Fowler et al, 2018 ; Hallaran et al, 2022 ; Levett-Jones & Lathlean, 2009 ), but a clear distinction for what it means to be ready to practice and create a sense of salience in this new healthcare field is greatly needed.…”
Section: Discussionmentioning
confidence: 99%
“…These learning outcomes should indicate what the student is expected to know, do or value by the time they have engaged in all teaching and learning activities and should inform the methods of assessment chosen (Goode, Hegarty & Levy 2018). Telerehabilitation is a clinical skill that we expected students to be able to use in practice (Currie et al 2022). Miller's pyramid was highly effective in guiding our thinking through the essential knowledge that students needed, what they needed to be able to do to facilitate a telerehabilitation session ethically and effectively and how the different programmes would implement telerehabilitation on the clinical training platform.…”
Section: Addressing the Training Needs Of Students Clinicians Clinica...mentioning
confidence: 99%
“…Miller's pyramid was highly effective in guiding our thinking through the essential knowledge that students needed, what they needed to be able to do to facilitate a telerehabilitation session ethically and effectively and how the different programmes would implement telerehabilitation on the clinical training platform. Therefore, a programme included several teaching and learning methods, including simulation and peer-review (Currie et al 2022). Our interprofessional approach was time efficient and produced a curriculum that was better than any of us could have developed independently.…”
Section: Addressing the Training Needs Of Students Clinicians Clinica...mentioning
confidence: 99%
“…RN preceptors are reported as key to successful entry-level nursing education programmes (Ulrich, 2019). A recent wideranging literature review of nursing education in Australia (Currie et al, 2019) confirmed nursing preceptorship to be a dominant and essential clinical teaching role supporting and assessing the practice of undergraduate and new graduate nurses. Despite an international research focus on the role and extensive reporting of role competencies and characteristics, Currie et al (2019) identified that nursing preceptors struggled to adequately prepare for the role and employers needed to define the role more closely.…”
Section: Introductionmentioning
confidence: 99%